Ventricular fibrillation as primary presentation of takotsubo cardiomyopathy after complicated cesarean delivery - Bortnik, Miriam (Baishideng Publishing Group Co., Limited, 2012)
Takotsubo cardiomyopathy typically affects post-menopausal women under severe psychological or physical stress; it also has been reported to develop after medical procedures or surgery. We herein report the rare case of a 30-year-old woman who presented with an episode of ventricular fibrillation after a very complicated cesarean delivery and was successfully resuscitated. Subsequent electrocardiography and echocardiography showed a typical Takotsubo pattern. Within 3 wk, left ventricular systolic function returned to normal.